An exploration of teacher leadership : a case study in a Namibian urban primary school - Zokka, Thomas Kayele (Rhodes University, Faculty of Education, Department of Education, 2013)
After independence in 1990, Namibian schools were required by the new government to shift from a hierarchical organisational structure with authoritarian leadership to a more democratic type of leadership that offers teachers the opportunity to participate in school leadership and in decision-making processes. This shift is suggested in a number of national policies in Namibia that highlight the sharing of leadership within the organization and, in particular, the sharing of leadership with teachers. As such, teacher leadership is a manifestation of distributed leadership which emphasizes that leadership can be located in the position of the principal but can spread over many people who work in a school at various levels. While teacher leadership is well researched in developed countries, it is under researched in Namibia. Against this backdrop, the purpose of my study was to explore the concept and practice of teacher leadership as an organizational phenomenon in a case study school in the Ncuncuni circuit of the Kavango region in Namibia. It also examined the factors that enabled and inhibited the practice of teacher leadership. My study was conducted within a qualitative interpretive paradigm and it adopted a case study approach in one school. The study used the following instruments to collect data: a closed questionnaire, document analysis, observations and individual interviews. The primary participants were the principal and three teachers, while the entire school teaching staff constituted my secondary participants. Quantitative data was analysed manually using descriptive statistics while qualitative data was analysed thematically using a model of teacher leadership (Grant, 2008). The findings of my study indicated that while the concept of teacher leadership was new to all participants, they had a common sense understanding of it. Although teachers in the study understood teacher leadership in a range of different ways, the overarching idea of the whole school was that teachers lead both in and outside the classroom. My study also found that teachers in the school practiced teacher leadership across the entire four zones. These included how teacher leadership was practiced inside the classroom and how teachers worked as leaders with colleagues and learners beyond their classroom in curricular and extra-curricular activities. It also included how teachers led outside their classroom in whole school development as well as how teachers led beyond their schools in the community. Teacher leadership was strong in the first three zones and weaker in the fourth zone, which constituted an example of 'successful teacher leadership' (Harris and Muijs, 2005). There were factors that promoted teacher leadership in the case study school such as a supportive culture and ongoing professional development. Factors that constrained the practice of teacher leadership were also evident like the SMT who used its power at times to control teachers' decisions and a lack of time also emerged as a barrier that impeded teachers from taking leadership roles because they already had full teaching programmes. Even though there were some barriers to teacher leadership, a dispersed distributed leadership context prevailed at the case study school.
Keywords: Educational leadership -- Namibia -- Kavango -- Case studies; Teacher participation in administration -- Namibia -- Kavango -- Case studies; School management and organization -- Namibia -- Kavango -- Case studies; Education, Elementary -- Namibia